1995
DOI: 10.1038/hdy.1995.106
|View full text |Cite
|
Sign up to set email alerts
|

Outcrossing rates and inferred levels of inbreeding depression in gynodioecious Cucurbita foetidissima (Cucurbitaceae)

Abstract: Sex-specific outcrossing rates and the inbreeding coefficient of adults in two populations of gynodioecious Cucurbita foetidissima were estimated using progeny array data from four allozyme loci to compare the frequencies of self-fertilization and the estimated levels of inbreeding depression to predictions from sex ratio theory. The frequencies of self-fertilization by hermaphrodites in both populations were similar and averaged 73 per cent. The outcrossing rate for females in one population was not different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 59 publications
(55 reference statements)
2
34
0
Order By: Relevance
“…Furthermore, stable persistence of male-sterility factors in the absence of a fecundity advantage would require a combination of very high levels of inbreeding depression and extensive hermaphrodite selfing (Lloyd, 1975;Charlesworth and Charlesworth, 1978). Simultaneous occurrence of extensive selfing of hermaphrodites and high inbreeding depression has also been reported for other gynodioecious plants like Plantago coronopus (Wolff et al, 1988), Cucurbita foetidissima (Kohn, 1988;Kohn and Biardi, 1995), Bidens sandvicensis (Schultz and Ganders, 1996), and Schiedea adamantis (Sakai et al, 1997). Results of this study are fully consistent with these expectations and indicate that explanations for the persistence of females in gynodioecious D. laureola need not be sought beyond the conventional theoretical framework.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, stable persistence of male-sterility factors in the absence of a fecundity advantage would require a combination of very high levels of inbreeding depression and extensive hermaphrodite selfing (Lloyd, 1975;Charlesworth and Charlesworth, 1978). Simultaneous occurrence of extensive selfing of hermaphrodites and high inbreeding depression has also been reported for other gynodioecious plants like Plantago coronopus (Wolff et al, 1988), Cucurbita foetidissima (Kohn, 1988;Kohn and Biardi, 1995), Bidens sandvicensis (Schultz and Ganders, 1996), and Schiedea adamantis (Sakai et al, 1997). Results of this study are fully consistent with these expectations and indicate that explanations for the persistence of females in gynodioecious D. laureola need not be sought beyond the conventional theoretical framework.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping in mind the limitations inherent to inferences about inbreeding depression levels based on genetic markers (Kohn and Biardi, 1995;Dorken et al, 2002, and references therein), this method is possibly the only applicable to obtain whole life cycle estimates for long-lived plants like D. laureola, where direct measurements of inbreeding depression beyond the earlier stages in the life cycles are impractical. Inbreeding depression levels in these earlier stages are often smaller (eg, Sakai et al, 1997) and, in fact, earlier investigations on D. laureola failed to demonstrate any measurable inbreeding depression effect on fruit set, fruit and seed size, seed germination, and early seedling survival (Alonso and Herrera, 2001; C Alonso, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have used the Ritland approach to estimate ID (Dole and Ritland, 1993;Eckert and Barrett, 1994;Kohn and Biardi, 1995;Scofield and Schultz, 2006;Tamaki et al, 2009;Yang and Hodges, 2010), a frequent criticism of the method is that ID estimates are typically encumbered with high statistical uncertainty. Confidence bands on ID estimates routinely span the entire range of possible values.…”
Section: Introductionmentioning
confidence: 99%
“…However, Robinson et al (1976) have reported that different types of sexual expression have influence on the natural outcrossing rate, since both natural outcrossing and selfing for the cucumber and melon can occur. Kohn and Biardi (1995) estimated a selfing rate of 73% in monoecious plants and 11.9% to 40.7% in gynoecious plants from two populations of Cucurbita foetidissima, a perennial cucurbitaceae that is native of the United States and Northeast Mexico. These estimates indicate a mixed mating system, which is intermediate in relation to autogamy and allogamy.…”
Section: Sexual Expression and Mating System In Watermelon: Implicatimentioning
confidence: 99%